Effect of sowing date on 'grain and fodder production of barnyard millet (Echinochloa crus-galli ssp' utilis) at high altitudes - BANDYOPADHYAY, B B (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1996-97 on the effect of sowing date on grain and fodder production among 21selected lines of barnyard millet [Echinochloa crus.galli (L.) p, Beauv. ssp utilis] cultivars at an altitude of 2 100 mabove mean sea-level on 3 sowing dates in April, May and June respectively. Sub-optimal temperature during vegetativeperiod at sowing date in April and May delayed the initiation of flowering. On the contrary, an early tennination ofgrowing season and prolong duration of grain filling was observed in June sowing at an exposure to low atmospherictemperature at post-floral growth of crop. Cultivars sown in April gave maximum grain and fodder yield. Correlationand path analysis suggested that sowing condition in April was more effective for greater exploitation of both grain andfodder yield of cultivars Under high hill condition.